Step-by-step explanation:
Step 1: Distribute the 3 to (x-4)
⇒ 3(x)-3(4) = 12
Step 2: Calculate the left side!!
⇒ 3x-12= 12
Step 3: Add 12 to both sides!
⇒ 3x= 24
Step 4: Divide 3 by both sides!
⇒ 3x/3= 24/3
Step 5: YOUR ANSWER!!
⇒ 8
ANSWER: 8
Which list contains only integers that are NOT also whole numbers?
F 4,-2, 0, 2,4
G-8, -6, -4,-2
H 2, 4, 6,8
J 1/8, 1/6, 1/4, 1/2
Answer:
G -8, -6, -4, -2
Step-by-step explanation:
integers are ...-2,-1,0,1,2,3 ... and so on but
whole numbers are 1,2,3,4,5,6 ... so on
so the only one thats right is the negative numbers
ANYONE GOOD AT FINDING RHOMBUS??
Answer:
x = 3
Step-by-step explanation:
The diagonals of a rhombus bisect each other at right angles, thus
BE = ED, that is
4x + 2 = 3x + 5 ( subtract 3x from both sides )
x + 2 = 5 ( subtract 2 from both sides )
x = 3
Since diagonals of rhombus bisect each other,
AC bisects BD into two equal parts
ie,
⇒BE=ED
⇒4x+2=3x+5
⇒4x-3x=5-2
⇒x=3
A direct variation function contains the points (–9, –3) and (–12, –4). Which equation represents the function?
Answer: y = x/3
Have a nice day!
Answer:
[tex]\displaystyle y = \frac{1}{3}x[/tex]
Step-by-step explanation:
First, find the rate of change [slope]:
[tex]\displaystyle \frac{-y_1 + y_2}{-x_1 + x_2} = m \\ \\ \frac{3 - 4}{9 - 12} = \frac{1}{3}[/tex]
Then plug these coordinates into the Slope-Intercept Formula instead of the Point-Slope Formula since you get it done much swiftly that way. It does not matter which ordered pair you choose:
−4 = ⅓[−12] + b
−4
[tex]\displaystyle ±0 = b \\ \\ y = \frac{1}{3}x[/tex]
_______________________________________________
−3 = ⅓[−9] + b
−3
[tex]\displaystyle ±0 = b \\ \\ y = \frac{1}{3}x[/tex]
**You see? I told you it did not matter which ordered pair you choose because you will ALWAYS get the exact same result.
I am joyous to assist you anytime.
Answer:
The answer is...
Step-by-step explanation:
y = 1/3x
--or--
y = x/3
Both forms of writing are equivalent, so either choice would be correct. I hope this helps!
when the polynomial f(x) is divided by (x-2) the remainder is 4, and when it is divided by (x-3) the remainder is 7. Given that f(x) may be written in the form f(x)= (x-2)(x-3)Q(x)+ax+b, find the remainder when f(x) is divided by (x-2)(x-3). If also f(x) is a cubic function in which the coefficient of x^3 is unity and f(1)=1, determine Q(x)
The remainder when a cubic polynomial is divided by (x-2)(x-3) can be found using the given remainders with (x-2) and (x-3) separately, resulting in a = 3 and b = -2. Hence, the remainder is 3x - 2. Then, using the condition that f(1)=1 and f(x) is cubic with a leading coefficient of 1, we can determine the entire function and Q(x).
Explanation:Given that a polynomial f(x) has remainders when divided by (x-2) and (x-3), we can establish that:
f(x) = (x-2)(x-3)Q(x) + ax + b, where a and b are constants that represent the remainder when f(x) is divided by (x-2)(x-3).The condition f(x) divided by (x-2) has remainder 4:f(2) = 4, which gives us (2-2)(2-3)Q(2) + 2a + b = 4.The condition f(x) divided by (x-3) has remainder 7: f(3) = 7, which gives us (3-2)(3-3)Q(3) + 3a + b = 7.From these conditions, we derive two equations:
2a + b = 43a + b = 7Solving these simultaneously gives us a = 3 and b = -2. Thus, the remainder when f(x) is divided by (x-2)(x-3) is 3x - 2.
Considering f(x) is cubic and the coefficient of x^3 is 1, f(x) = x^3 + px^2 + qx + r, and since f(1)=1, we can find out Q(x) by plugging the values a, b, and f(1) into the polynomial f(x) and comparing it with the standard cubic form. This will lead us to determine the function Q(x).
Please explain answer to the math question in the picture thanks so much!
Answer:
[tex]m = -6 \ or \ m = -\frac{1}{4}[/tex]
Step-by-step explanation:
Given
[tex]\frac{1}{m^2+7m+6}+\frac{m+3}{m^2+7m+6}= \frac{5}{m+6}\\[/tex]
Simplifying the above equation we get:
Step 1: Solving for common denominator term we get;
[tex]\frac{1+m+3}{m^2+7m+6}= \frac{5}{m+6}\\\\\frac{m+4}{m^2+7m+6}= \frac{5}{m+6}[/tex]
Step 2: Multiplying denominators on both side we get;
[tex](m+4)(m+6)=5(m^2+7m+6)\\m^2+6m+4m+24 = 5m^2+35m+30\\m^2+10m+24 = 5m^2+35m+30\\5m^2+35m+30-m^2-10m-24=0\\4m^2+25m+6=0[/tex]
Step 3: Now we need to find the factors of m.
[tex]4m^2+25m+6=0\\4m^2+m +24m+6=0\\m(4m+1)+6(4m+1)=0\\(4m+1)(m+6)=0[/tex]
Step 4: Solving for both terms we get;
[tex]4m+1=0\\4m =-1\\m= - \frac{1}{4}[/tex]
Also,
[tex]m+6=0\\m=-6[/tex]
Hence [tex]m = -6 \ or \ m = -\frac{1}{4}[/tex]
5x + 9 = x - 23 find X
5x + 9 = x - 23
move x to the other side
sign changes from +x to -x
5x-x+9= x-x-23 ( combine like terms)
5x-x+9= -23
4x+9= -23
move -9 to the other side
4x+9-9= -23-9
4x= -23-9
4x= -32
divide both sides by 4 to get x by itself
4x/4= -32/4
answer:
x= -8
Kaelyn has some yarn that she wants to use to make hats and scarves. Each hat uses 0.2 kilograms of yarn and each scarf uses 0.1 kilograms of yarn. Kaelyn wants to make 3 times as many scarves as hats and use 5 kilograms of yarn. Let h be the number of hats Kaelyn makes and s be the number of scarves she makes.
Answer:
10 hats and 30 scarves
Step-by-step explanation:
Let h be the number of hats Kaelyn makes and s be the number of scarves she makes.
Kaelyn wants to make 3 times as many scarves as hats, so
s = 3h
Each hat uses 0.2 kilograms of yarn, then h hats use 0.2h kg of yarn.
Each scarf uses 0.1 kilograms of yarn, then s scarves use 0.1s kg of yarn.
Kaelyn wants to use 5 kilograms of yarn, thus
0.2h + 0.1s = 5
You get the system of two equations:
[tex]\left\{\begin{array}{l}s=3h\\ \\0.2h+0.1s=5\end{array}\right.[/tex]
Substitute the first equation into the second
[tex]0.2h+0.1\cdot 3h=5\\ \\0.2h+0.3h=5\\ \\0.5h=5\\ \\5h=50\\ \\h=10\\ \\s=3\cdot 10=30[/tex]
Answer:
s=3h
0.2h+0.1s=15
Step-by-step explanation:
The expression 1,000(1.0175)2+ describes the amount of money in a savings account after years. Complete the statements.
each year.
The Interest rate is compounded_____each year
1- 1 time
2-2 times
3- 4 times
4- 12 times
The annual Interest rate on the account is ____
1- 1.75%
2- 3.50%
3- 3.53%
4- 3.56%
Answer:
a) 1 time
b) 1.75%
Step-by-step explanation:
a) The given expression is 1,000(1.0175)^2
Here,
1,000 is the principal (Present Value); (1.0175 = 1 + 0.0175) is the compounding interest rate; and 2 is the number of period (Years).
Since two means 2nd year, therefore, the interest is compounded every year. Hence, it is annual compounding interest.
If the interest rate is compounded annually, the interest will be paid one time each year or period.
b) From part a, if we break the expression,
1,000 is the principal (Present Value); (1.0175 = 1 + 0.0175) is the compounding interest rate; and 2 is the number of period (Years).
Since the interest rate is to be compounded annually, the percentage will not affect.
(1.0175 = 1 + 0.0175) in this expression, one is added to the interest to make the future compounding value.
Therefore, 0.0175 is the interest rate. If we take it to the percentage -
0.0175 x 100 = 1.75%.
Answer:
a) 1 time
b) 1.75%
Step-by-step explanation:
yes
X divided by X+4 =.6666
Answer:
x = 8
Step-by-step explanation:
x/x+4=2/3
3x = 2x + 8
x = 8
school started at 8:05 a.m and ended at 2:40p.m. the work below shows Erica's calculation of the length of the school day
Which two errors did erica make
A.She subtracted instead of adding the times
B.She subtracted the end time from the start time
C.She did not regroup on hours for 60 minutes to subtract the minutes
D.she did not account for a.m. and p.m. in the start and end times.
E.see switch to hours and minutes in both the start and end times
Plz help▪~▪
Answer:
B. She subtracted the end time from the start time and
D. She did not account for a.m. and p.m. in the start and end times.
Step-by-step explanation:
The school started at 8:05 a.m. and ended at 2:40 p.m.
And the length of the school day is calculated by Erica and it is shown in the attached photo.
See the attached photo.
Erica has done two errors which are
B. She subtracted the end time from the start time and
D. She did not account for a.m. and p.m. in the start and end times. (Answer)
What is the slope of this graph?
−3
−13
3
13
Answer:
-3
Step-by-step explanation:
start at the y axis where x= 0, go over one and down till your reach the next intersection of the graph, this is over one down three, or -3 for every x over
which of the following is not a condition of the binomial distribution?
Conditions of the binomial distribution include a fixed number of independent trials, each trial having two possible outcomes, and constant probabilities of success and failure. Experiments that do not meet these conditions do not follow a binomial distribution. For example, if the probability of success varies across trials, it's not a binomial distribution.
Explanation:The binomial distribution has several key conditions, and a statistical experiment is classified as a binomial experiment if it meets these conditions. Some of these conditions include the following:
There is a fixed number of trials, often denoted with the letter 'n' Each trial is independent, meaning the result of any one trial does not affect the results of the following trials Each trial has only two possible outcomes: success and failure The probability of success (denoted 'p') and failure (denoted 'q') are consistent across trials
Therefore a circumstance not meeting these conditions would not fit the binomial distribution. For example, if the conditions for each trial are not consistent, such as the probability of success changes from trial to trial, then it would not be classified as a binomial distribution.
Learn more about Binomial Distribution here:https://brainly.com/question/33656163
#SPJ3
ABCD is a parallelogram. Find the measure of B.
Answer:
∠B = 130°
Step-by-step explanation:
The opposite angles of a parallelogram are congruent, thus
∠D = ∠B, that is
10x - 20 = 9x - 5 ( subtract 9x from both sides )
x - 20 = - 5 ( add 20 to both sides )
x = 15
Hence
∠B = 9x - 5 = (9 × 15) - 5 = 135 - 5 = 130°
Answer:
15
Step-by-step explanation:
9x-5=10x-20
X-20=-5
X=15
what is the y-intercept of the points (-3, 2) and (-2, -4) ?
Answer: -16
Step-by-step explanation:
slope=rise/run
slope=2-(-4)/-3-(-2)=6/-1=-6
y=mx+b
2=(-6)-3+b
b=-16
Answer:
3_561938 you are your
Step-by-step explanation:
3AM said
PLEASE HURRY!!
Two hot air balloons are traveling along the same path away from a town,
beginning from different locations at the same time. Henry's balloon begins
30 miles from the town and is 48 miles from the town after 2 hours. The
distance of Tasha's balloon from the town is represented by the function y =
8x+ 20.
Whích balloon was farther from the town at the beginning, and which traveled
more quickly?
O
A. Tasha's balloon was farther from the town at the beginning, but
Henry's balloon traveled more quickly.
O
B. Tasha's balloon was farther from the town at the beginning, and it
traveled more quickly.
O
C. Henry's balloon was farther from the town at the beginning, but
Tasha's balloon traveled more quickly.
O
D. Henry's balloon was farther from the town at the beginning, and it
traveled more quickly.
Henry's balloon was farther from the town at the beginning, but Tasha's balloon traveled more quickly.
Explanation:To determine which balloon was farther from the town at the beginning, we need to compare the initial distances of Henry's and Tasha's balloons from the town. Henry's balloon begins 30 miles from the town, while Tasha's balloon is represented by the function y = 8x + 20, where x is the time in hours. Plugging in x = 0 into the function, we can find that Tasha's balloon was 20 miles from the town at the beginning.
To determine which balloon traveled more quickly, we can compare their speeds. Henry's balloon travels at a constant speed of (48 miles - 30 miles) / 2 hours = 9 miles/hour. Tasha's balloon has a constant speed of 8 miles/hour since it follows the equation y = 8x + 20. Therefore, Henry's balloon traveled more quickly.
Therefore, the correct answer is OC. Henry's balloon was farther from the town at the beginning, but Tasha's balloon traveled more quickly.
Permutations & Cominations:
Your friend is having a party and has 15 games to choose from. There is enough time to play 4 games. In how many ways can you choose the four games?
Answer:
32760 ways
Step-by-step explanation:
Suppose we all want to play different games, so 4 different games. At the first game there are 15 choices, at the 2nd game there are 14, the 3rd one there are 13 selections, and at the last there are only 12 options to select from. Then the total number of ways you can choose the 4 games is
15*14*13*12 = 32760 ways
There are 1,365 ways to choose four games out of the 15 available games.
Step 1
To find the number of ways you can choose four games out of the 15 available games, we use the combination formula:
[tex]\[ C(n, k) = \frac{n!}{k!(n-k)!} \][/tex]
Where n is the total number of games (15) and k is the number of games to choose (4).
Step 2
Plugging in the values:
[tex]\[ C(15, 4) = \frac{15!}{4!(15-4)!} \][/tex]
[tex]\[ = \frac{15!}{4! \times 11!} \][/tex]
[tex]\[ = \frac{15 \times 14 \times 13 \times 12}{4 \times 3 \times 2 \times 1} \][/tex]
[tex]\[ = \frac{32,760}{24} \][/tex]
[tex]\[ = 1,365 \][/tex]
You can choose the four games out of the 15 available games in 1,365 ways, calculated using the combination formula.
The result of which expression will best estimate the actual product
06-1(4)-10-1)
06-1(4)-100
Save and Exit
Next
Submit
Mark this and return
SA
A
6
) ENG
O
Type here to search
Answer:
The answer is,
[tex](-1) \times \frac {1}{2} \times (-1) \times (1)[/tex]
Step-by-step explanation:
The given product is,
[tex]\frac {-4}{5} \times \frac{3}{5} \times \frac{-6}{7} \times \frac {5}{6}[/tex]
= [tex]\frac {12}{35}[/tex]
[tex]\simeq 0.3429[/tex] ---------------------(1)
Now, the first product to compare is,
[tex](-1) \times \frac {1}{4} \times (-1) \times (-1)[/tex]
= - 0.25 ----------------------------(2)
The second product to compare is,
[tex](-1) \times \frac {1}{2} \times (-1) \times (1)[/tex]
= 0.5 ------------------------(3)
The 3rd product to compare is,
[tex]\frac {-4}{2} \times \frac {3}{2} \times \frac{-2}{5} \times \frac {5}{2}[/tex]
= 3 ----------------------------(4)
The 4th product to compare is,
[tex]\frac {-3}{4} \times \frac {-3}{4} \times \frac {-1}{5} \times \frac {1}{2}[/tex]
= [tex]\frac {-9}{160}[/tex]
= 0.05625 -----------------(5)
Comparing all the values , we get (3) is closest to (1).
Hence, we get, the answer is,
[tex](-1) \times \frac {1}{2} \times (-1) \times (1)[/tex]
A pan of brownies was left out on the counter and 1/4 of the brownies had alreary been eaten. Then John came along and ate 2/3 of the brownies that were left. How much of the whole pan of brownies did John eat?
Answer:
1/4 of the brownies were eaten
there were 1 - 1/4 = 3/4 of brownies left
2/3 of the 3/4 were eat or: (2/3)(3/4) = 1/2 of the whole pan of brownies were eaten
the total of brownies eaten is: 1/4 + 1/2 = (1*1 + 2*1)/4 = 3/4 of the whole pan of brownies were eaten.Step-by-step explanation:
John ate half or 50% of the original whole pan of brownies. This is calculated by multiplying 3/4 (the remaining brownies after 1/4 had been eaten) by 2/3 (the fraction John ate of the remaining amount).
Explanation:Firstly, the question pertains to the proportion of brownies that were consumed. Initially 1/4 of the brownies were eaten, implying that 3/4 of the brownies were left on the counter. John ate 2/3 of the remaining brownies, so we will calculate 2/3 of 3/4 to determine how much of the whole pan of brownies John ate:
Step 1: Convert 3/4 and 2/3 to decimal points (0.75 and 0.67 respectively).
Step 2: Multiply 0.75 (the remaining brownies) by 0.67 (the fraction that John consumed). This equals approximately 0.50.
Step 3: The result 0.50 implies that John consumed 50% or half of the original brownies amount.
Learn more about Fraction Multiplicationhttps://brainly.com/question/33564650
#SPJ2
Bobby believes his video game scores are clustered
closer to his median than Amelia's are to her median.
Explain why you agree or do not agree with Bobby.
Lower Quartile
Upper Quartile
Median
Bobby
472
585
535
Amelia
454
633
535
Answer: Bobby’s interquartile range is 113, while Amelia’s is 179. A lower interquartile range means Bobby’s scores are closer to the median.
Step-by-step explanation:
Answer:
his rang is 113 and amelis is 179
Step-by-step explanation:
PLS HELP ASAP I WILL GIVE BRAINERLIST
Answer:
4
Step-by-step explanation:
if x = 32 and y = 2, then you just have to substitute the numbers in:
[tex]\frac{32}{4 * 2}[/tex]
so,
[tex]\frac{32}{8}[/tex]
then you simplify
[tex]\frac{4}{1}[/tex]
so the answer is 4
Answer:
2
Step-by-step explanation:
Replace the variables with the real numbers
32/4 2
Multiply
4 x 3 = 12
Divide
32 / 12 = 2⅔
2⅔ ≈ 2
Answer: 2
Edit: Instead, go with D.) 4
Profit is always calculated as revenue minus expenses. If a company’s expenses were $10 million, write an equation that expresses profit, P, (in millions of dollars) in terms of revenue, R, (in millions of dollars). Then, determine the profit when revenue is $25 million.
The equation that expresses profit, P, (in millions of dollars) in terms of revenue, R, (in millions of dollars) is P = R - 10
The profit is $15 million when revenue is $25 million
Step-by-step explanation:
The formula of the profit is P = R - E, where
R is the revenueE is the expensesIf a company’s expenses were $10 million, wee need to write an equation that expresses profit, P, (in millions of dollars) in terms of revenue, R, (in millions of dollars) and then find the profit when revenue is $25 million
∵ P is the profit in millions of dollars
∵ R is the revenue in millions of dollars
∵ The expenses E were $10 million
∵ Profit = Revenue - Expenses
∴ P = R - 10
The equation that expresses profit, P, (in millions of dollars) in terms of revenue, R, (in millions of dollars) is P = R - 10
∵ The revenue R = $25 million
∵ P = R - 10
- Substitute the value of R in the equation
∴ P = 25 - 10
∴ P = 15
∴ The profit is $15 million
The profit is $15 million when revenue is $25 million
Learn more:
You can earn more about the word problems in brainly.com/question/10557938
#LearnwithBrainly
What are the center and vertices of the ellipse given by (x-10)^2/49+(y+4)^2/4=1?
The center of the ellipse is (10 , -4) and its vertices are (17 , -4) , (3 , -4)
Step-by-step explanation:
The standard form of the equation of an ellipse with center (h , k)
and major axis parallel to x-axis is [tex]\frac{(x-h)^{2}}{a^{2}}+\frac{(y-k)^{2}}{b^{2}}=1[/tex]
The coordinates of the vertices are (h ± a , k ) The coordinates of the foci are (h ± c , k), where c² = a² - b²∵ The equation of the ellipse is [tex]\frac{(x-10)^{2}}{49}+\frac{(y+4)^{2}}{4}=1[/tex]
- Compare it by the standard form of the equation of an ellipse
∴ h = 10 and k = -4
∴ a² = 49 and b² = 4
∵ The center of the ellipse is (h , k)
∴ The center of the ellipse is (10 , -4)
∵ Its vertices are (h + a , k) and (h - a , k)
∵ a² = 49
- Take square root for both sides
∴ a = 7
∵ h = 10 and k = -4
- Substitute the values of h , a , k in the vertices above
∴ Its vertices are (10 + 7 , -4) and (10 - 7 , -4)
∴ Its vertices are (17 , -4) and (3 , -4)
The center of the ellipse is (10 , -4) and its vertices are (17 , -4) ,
(3 , -4)
Learn more:
You can learn more about the conics in brainly.com/question/4054269
#LearnwithBrainly
what number is 84% of 106?
Answer:
89.04Step-by-step explanation:
[tex]_{\bold{METHOD\ 1}}\\\\\begin{array}{ccc}100\%&-&106\\\\84\%&-&x\end{array}\qquad\text{cross multiply}\\\\\\100x=(84)(106)\\\\100x=8904\qquad\text{divide both sides by 100}\\\\\dfrac{100x}{100}=\dfrac{8904}{100}\\\\x=89.04[/tex]
[tex]_{\bold{METHOD\ 2}}\\\\p\%=\dfrac{p}{100}\to84\%=\dfrac{84}{100}=0.84\\\\84\%\ of\ 106=0.84\cdot106=89.04[/tex]
Jim currently has 1,250 in his bank account and Sally has 1,400 her bank account. Jim deposits 27,50 per week and Sally deposits 20 per week into her account. After how many weeks will they have the same amount of money?
Answer:
In 20 weeks they will have the same amount of money.
Step-by-step explanation:
A building is 2 ft from a 7 - ft fence that surrounds the property . A worker wants to wash a window in the building 11 ft from the ground . He plans to place a ladder over the fence so it rests against the building . (See the figure .) He decides he should place the ladder 7 ft from the fence for stability . To the nearest tenth of a foot , how long a ladder will he need ?
Answer:
The ladder is approx 14.21 feet long.
Step-by-step explanation:
The base of the ladder is 7 feet from the fence, which is 2 feet from the building, so it will be 9 feet from the building.
The top of the ladder will reach the window which is 11 feet from the ground.
In this way, we get a right triangle with the ladder as the hypotenuse, that we have to find.
Let the hypotenuse be x.
Using the Pythagorean Theorem, we get;
Hence, the ladder is approx 14.21 feet long.
Only 6 pleasee it’s due tomorrow thanks
Answer:
a) The amount of edging needed = 7.54 meters
b) Cost to edge the garden = $32.80
Step-by-step explanation:
a)
the amount of edging needed is basically the circumference (perimeter) of the circle. It has the formula:
[tex]C=2\pi r[/tex]
Where
C is the circumference
r is the radius
Given, diameter = 2.4, radius is HALF of it, so
r = 2.4/2 = 1.2
Now, finding circumference:
[tex]C=2\pi r\\C=2\pi (1.2)\\C=7.54[/tex]
The amount of edging needed = 7.54 meters
b)
$4.35 is needed to edge 1 meter, since we need 7.54 meters, we find the total cost by multiplying 4.35 with 7.54, so we have:
4.35*7.54 = $32.80
Cost to edge the garden = $32.80
Choose the statement beloe that lists the sides in order from Least to Greatest.
A.) SU, TU, ST
B.) TU, ST, SU
C.) TU, SU, ST
D.) ST, SU, TU
Option A: SU, TU, ST is the right answer
Step-by-step explanation:
In a triangle
The largest side and the largest angle are opposite to each otherThe shortest side and the shortest angle are opposite to each other.So using the above axioms we can observe the triangle.
The largest angle is m∠U = 80° so the side opposite to it is the largest i.e. ST is the largestThe smallest angle is m∠T = 25° so the shortest side is SU The third side will be the middle side as the angle ∠S is greater than 25° and less than 80°So the sides in order from least to greatest are: SU, TU, ST
Hence,
Option A: SU, TU, ST is the right answer
Keywords: Geometry, Triangles
Learn more about triangles at:
brainly.com/question/10941043brainly.com/question/10978510#LearnwithBrainly
Write an equation of the line that passes through the points (2, -1) and (2, 5). Show all work
Answer:
x = 2
Step-by-step explanation:
The 2 coordinate points have the same x- coordinate of 2
This indicates that the line passing through them is vertical with equation
x = c
Where c is the value of the x- coordinates the line passes through, thus
x = 2 ← equation of line
Renae likes to make pizza dough on the weekends.She has 3 3/4 cups of flour.She needs 3/8 of a cup of each pizza.How many whole pizzas can she make?
Answer:
10
Step-by-step explanation:
3 3/4=15/4
(15/4)/(3/8)=(15/4)(8/3)=30/3=10
Original price of a suit: $250.00
Discount: 25%
Tax: 8%
How much will you pay?
Answer:
207,50
Step-by-step explanation:
1% = 2,5
2,5x25 = 62,5 250 - 62,5 = 187,5
2,5x8 = 20
187,5+20= 207,50